Problem-Based Learning Worksheets to Improve Concept Understanding Skills of Sixth-Grade Elementary School Students - Rohman, Fatkhur; Putri, Tiya Permana; Ovita, Dhea; Larasati, Sattya Dewi; Nurhanurawati, Nurhanurawati (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2025)
This research is motivated by the lack of skills in understanding mathematical concepts among sixth-grade elementary school students. This study aims to develop Problem-Based Learning worksheets to improve the concept understanding skills of sixth-grade elementary school students. The research subjects are 30 sixth-grade students at SDN 2 Sido Binangun. The development stages of the method used in this research are Research and Development (R&D) with the ADDIE model. The instruments used in this research are validation sheets, student response questionnaires, and teacher response questionnaires. The research data consists of questionnaire results, the feasibility of the worksheets, and the responses of students and teachers, which are analyzed qualitatively and descriptively based on score criteria. The results show that Problem-Based Learning worksheets can improve students' concept understanding with an N-Gain of 0.63. Therefore, it can be concluded that Problem-Based Learning worksheets can enhance the concept-understanding skills of sixth-grade elementary school students.